Association of socioeconomic position with smoking and mortality: the contribution of early life circumstances in the 1946 birth cohort. Issue 3 (18th November 2013) - Giesinger, Ingrid; Goldblatt, Peter; Howden-Chapman, Philippa; Marmot, Michael; Kuh, Diana; Brunner, Eric
Abstract : Background: A large part of the socioeconomic mortality gradient can be statistically accounted for by social patterning of adult health behaviours. However, this statistical explanation does not consider the early life origins of unhealthy behaviours and increased mortality risk. Methods: Analysis is based on 2132 members of the MRC National Survey of Health and Development with mortality follow-up and complete data. Smoking behaviour was summarised by pack-years of exposure. Socioeconomic circumstances were measured in childhood (father's social class (age 4), maternal education (age 6)) and age 26 (education attainment, home ownership, head of household social class). We estimated the direct effect of early circumstances, the indirect effect through smoking and the independent direct effect of smoking on inequality in all-cause mortality from age 26 to 66. Results: Mortality risk was higher in those with lower socioeconomic position at age 26, with a sex-adjusted HR (relative index of inequality) of 1.97 (95% CI 1.18 to 3.28). Smoking and early life socioeconomic indicators together explained 74% of the socioeconomic gradient in mortality (the gradient). Early life circumstances explained 47% of the gradient, 23.5% directly and 23.0% indirectly through smoking. The explanatory power of smoking behaviour for the gradient was reduced from 50.8% to 28% when early life circumstances were added to the model. Conclusions: Early life socioeconomic circumstances contributed importantly to social inequality in adult mortality. Our life-course model focusing on smoking provides evidence that social inequalities in health will persist unless prevention strategies tackle the intergenerational transmission of disadvantage and risk.